2023
DOI: 10.1590/0102-311xen131022
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian National Food and Nutritional Security System: what are the similarities in the decentralization process?

Abstract: This study aimed to analyze the multiple characteristics of the decentralization of the Brazilian National Food and Nutritional Security System (SISAN) in a period before the institutional dismantling. Data from the 26 Brazilian states were collected in two public information systems, referring to the years 2017/2018. An exploratory and descriptive study was performed using a hierarchical cluster analysis, based on an analysis model with multiple characteristics of the system decentralization. The results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The decentralization of public policies in Brazil since the 1990s is considered an appropriate measure as it has helped overcome barriers in implementing local policies. However, decentralization has its limits when the political, administrative, social, cultural, and ecological characteristics of different regions in Brazil are not taken into account [17,28].…”
Section: Decentralization and Government Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The decentralization of public policies in Brazil since the 1990s is considered an appropriate measure as it has helped overcome barriers in implementing local policies. However, decentralization has its limits when the political, administrative, social, cultural, and ecological characteristics of different regions in Brazil are not taken into account [17,28].…”
Section: Decentralization and Government Managementmentioning
confidence: 99%
“…Martins et al [28], in grouping Brazilian states into clusters of similarity regarding different aspects of decentralized SISAN governance, identified that states with a higher intersectoral and participatory character in SISAN governance were the same ones with better relationships with their municipalities and better resource allocation. Conversely, states with a lower intersectoral and participatory character were associated with low resource allocation and implementation of food security actions, as well as weak support for SISAN decentralization at the municipal level.…”
Section: Decentralization and Government Managementmentioning
confidence: 99%